Calcified Cerebral Emboli - Kavanagh, E.C. (AJNR Am J Neuroradiol, 2006)
SUMMARY: Intracranial calcifications may represent calcified cerebral emboli. Calcified emboli may be overlooked even though cerebral CT is widely used as a stroke assessment. We report 4 cases of calcified cerebral emboli and demonstrate the value of CT in the diagnosis and temporal evaluation of such emboli.